Imperfection sensitivity of post-buckling of FML channel section column. (May 2017) - Mania, Radoslaw J.; Madeo, Antonio; Zucco, Giovanni; Kubiak, Tomasz
Abstract: In the paper the post-buckling behaviour of thin-walled channel cross-section columns made of Fiber Metal Laminate subjected to an axial compressions is considered. The main interest is focused on the initial imperfection influence on the post-buckling response and thus the sensitivity analysis with application of Monte Carlo simulations is performed. A different shapes and amplitudes of geometrical imperfections – all corresponding to a particular buckling mode or to a few superimposed, have been applied in numerical models. The numerical simulations have been performed using developed FEM software based on Koiter's asymptotic theory for hundreds of buckling mode cases. The obtained results of numerical calculation have been compared with results of experimental investigations. Both - the numerical computations and laboratory experiments were performed on short FML channel section columns with four different layer arrangements. The strain-gauge technique, laser measurement and digital image correlation system were employed to determine deformation modes in laboratory tests. A comparison of the results shows that geometrical imperfections have substantial impact on the post-buckling response of considered columns. Highlights: Investigation of buckling and post-buckling response of thin-walled Fiber Metal Laminates members. Application of modified Koiter's method. The Monte Carlo simulation of different shape and amplitude of geometrical imperfections. Comparison of results determined from analytical and numerical method with experiment investigations. Application of obtained conclusions for modelling buckling response of FML profiles.